Absolute flow and resistance have a lower variability in repeated testing as compared to CFR and IMR: an EDIT-CMD substudy. (3rd October 2022) - Jansen, T P J; De Vos, A; Damman, P; Paradies, V; Konst, R E; Teerenstra, S; Van Den Oord, S C H; Dimitriu-Leen, A; Maas, A H E M; Smits, P C; Elias-Smale, S E; Van Royen, N
Abstract: Background: Invasive coronary function testing (CFT), including both acetylcholine (ACH) spasm provocation testing and assessment of coronary flow and resistance, is recommended to assess coronary vasomotor dysfunction (CVDys) in patients with angina and non-obstructive coronary artery disease (ANOCA). Objectives: To determine repeat testing reliability of invasive measurements of CVDys. Methods: In the EDIT-CMD trial, 73 patients underwent both baseline and follow-up CFT after six weeks. Repeat testing reliability for CVDys assessment, including coronary flow reserve (CFR), index of microvascular resistance (IMR), absolute flow (Q) and microvascular resistance (R) was assessed by 1.) comparing continuous values between baseline and follow-up measurement, including difference and correlation between the two measurements 2.) classification agreement (CCA) for the presence of CMD according to cut-offs, which was also assessed for ACH spasm provocation test and 3.) Bland-Altman plots. Fisher-Z scores were used to compare correlations. Results: Mean CFR was 3.1±1.5 at baseline and 4.1±1.5 at follow-up (P=0.03), with no significant correlation (ρ=0.285, P=0.10). Mean IMR was 27±12 at baseline and 27±19 at follow-up (P=0.94), with a trend to a significant correlation (ρ=0.312, P=0.07). The CCA between the baseline and follow-up was 74% for CFR and 57% for IMR. Mean Q was 183±72 at baseline and 192±78 at follow-up (P=0.49), with a significant correlation (ρ=0.579, P<0.001). Mean R was 527±233 at baseline and 506±228 at follow-up (P=0.67), with a significant correlation (ρ=0.51, p=0.03). The CCA between R at baseline and 6 weeks follow-up was 72% and for Q this was 82%. The correlation coefficient (ρ) of Q was significantly better than the ρ of CFR (P=0.006). The ρ of R and IMR did not differ. For the ACH spasm provocation test we found a CCA of 79% between both measurements. Conclusion: This is the first study to assess re-test reliability of the invasive CFT. Measurements of Q and R show higher agreement and correlation than their surrogates CFR and IMR in assessing microvascular function. ACH provocation spasm test also demonstrated good re-test reliability. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott